2008
DOI: 10.1007/s11120-007-9287-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of initial chlorophyll fluorescence induction kinetics in chloroplasts in terms of rate constants of donor side quenching release and electron trapping in photosystem II

Abstract: The fluorescence induction F(t) of dark-adapted chloroplasts has been studied in multi-turnover 1 s light flashes (MTFs). A theoretical expression for the initial fluorescence rise is derived from a set of rate equations that describes the sequence of transfer steps associated with the reduction of the primary quinone acceptor Q A and the release of photochemical fluorescence quenching of photosystem II (PSII). The initial F(t) rise in the hundreds of ls time range is shown to follow the theoretical function d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…Tóth et al (2007b) showed that the relation between F J and the area between the OJ rise and F M as a function of the extent of anaerobiosis was linear, indicating that at the F J step connectivity no longer affects the fluorescence rise. It has also been suggested that the sigmoidicity of the initial fluorescence rise, which is interpreted to be consequence of connectivity (reviewed by Stirbet 2013) can alternatively be explained on the basis of two overlapping exponential reactions (Vredenberg 2008; Schansker et al 2011). This can account for the disappearance of the sigmoidicity of the fluorescence rise when the temperature is lowered to −10 °C (Schansker et al 2011).…”
Section: Question 9: How Can Photochemical Quenching Be Defined and Wmentioning
confidence: 99%
“…Tóth et al (2007b) showed that the relation between F J and the area between the OJ rise and F M as a function of the extent of anaerobiosis was linear, indicating that at the F J step connectivity no longer affects the fluorescence rise. It has also been suggested that the sigmoidicity of the initial fluorescence rise, which is interpreted to be consequence of connectivity (reviewed by Stirbet 2013) can alternatively be explained on the basis of two overlapping exponential reactions (Vredenberg 2008; Schansker et al 2011). This can account for the disappearance of the sigmoidicity of the fluorescence rise when the temperature is lowered to −10 °C (Schansker et al 2011).…”
Section: Question 9: How Can Photochemical Quenching Be Defined and Wmentioning
confidence: 99%
“…DCMU and several other compounds are known to replace irreversibly Q B from its pocket, blocking the reoxidation of reduced Q A and interrupting the connection between PSII and PSI (Velthuys 1981;Vermaas et al 1984). The FI curves measured in the presence of DCMU are simpler and, thus, easier to be described theoretically than the O-J-I-P curves, although there is no consensus on the interpretation for the origin of sigmoidicity in the DCMU curve (Joliot and Joliot 1964;Strasser 1978Strasser , 1981Vredenberg 2000Vredenberg , 2008bSchansker et al 2011). Further, questions remain regarding the multi-exponential fluorescence kinetics as being due to PSII heterogeneity Homann 1975, 1976;Lazár and Pospíšil 1999), or other causes, which will not be discussed here.…”
Section: The Fast Fluorescence Transient Of Dcmu-treated Samples: Doementioning
confidence: 99%
“…The so-called TSTM advocated by Vredenberg (2000Vredenberg ( , 2004Vredenberg ( , 2008b has the following assumptions and concepts:…”
Section: Is Y Zmentioning
confidence: 99%
“…3d). Because of the high signal-to-noise ratio and time resolution, the commonly used three main parameters can be well recognized and easily determined from the kinetics of the fluorescence induction: (1) the lag phase which is characteristic to the connectivity of the photosynthetic units (although this view is challenged recently (Vredenberg 2008), (2) the rise time that is related to the absorption cross section of the light harvesting system and (3) the variable part of the fluorescence that reflects the effectiveness of capture of the photons to photochemistry. While the fluorescence induction describes relatively simple kinetics, that of the dark relaxation shows complex behavior and the time range extends over several orders of magnitude indicating strong deviation from a single exponential kinetics.…”
Section: Variable Fluorescence Of Intact Cellsmentioning
confidence: 99%